Aramid fiber III molecule coated multi-walled carbon nanotube composite fiber and preparation method thereof
By performing activation pretreatment, lossless dispersion and post-treatment of multi-walled carbon nanotubes, poor dispersion and fiber defects caused by carbon nanotube agglomeration are solved, and multi-walled carbon nanotube composite fibers are realized with high strength and high toughness.
Patent Information
- Application Number
- CN202311271899.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, carbon nanotubes are prone to agglomeration during spinning, resulting in poor dispersion, introducing internal defects of fibers, affecting the integrity and tensile strength of fibers.
Through the activation pretreatment, lossless dispersion and post-treatment steps of multi-wall carbon nanotubes, monodispersion of carbon nanotubes is achieved, agglomeration is avoided, and dispersion is improved.
The agglomerated carbon nanotubes are effectively removed, and the strength and toughness of aramid fibers are improved. The composite fibers obtained have a strength of more than 37cN/dtex and an elongation of break of more than 4%.
Smart Images

Figure CN119710959A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon materials, and in particular relates to a multi-walled carbon nanotube composite fiber wrapped with aramid III molecules and a preparation method thereof. Background Art
[0002] The preparation of carbon nanotube / aramid composite fibers by wet spinning has been studied in the prior art. For example, in the technical solution of the prior art CN114197076A, m-phenylenediamine and carbon nanotubes are simultaneously added to an amide polar organic solvent for dissolution, but solid, high-viscosity m-phenylenediamine easily induces agglomeration of carbon nanotubes, resulting in poor dispersion of carbon nanotubes; secondly, the agglomerated carbon nanotubes are large in size, which will introduce defects into the fiber during the subsequent wet spinning process, causing broken fibers, seriously affecting the integrity of the aramid fibers obtained by subsequent spinning and reducing their tensile strength. Summary of the invention
[0003] In order to solve the problems in the prior art, the present invention provides a method for preparing a multi-walled carbon nanotube composite fiber wrapped with aramid III molecules, which specifically comprises the following steps:
[0004] (1) Activation pretreatment of multi-walled carbon nanotubes: dissolving the multi-walled carbon nanotubes in a N,N-dimethylformamide solution containing LiCl, and treating them with a cell crusher for 10-30 minutes under N2 protection to obtain a multi-walled carbon nanotube solution;
[0005] (2) Dilution treatment of aramid III polymer solution: using a DMAC / LiCl solution of the same concentration as in step (1) to dilute the aramid III polymer solution having a viscosity of 30,000 to 120,000 centipoise to 1,000 to 5,000 centipoise by cell crushing or mechanical stirring, so that the molecular chains are evenly dispersed in the solvent;
[0006] (3) Nondestructive dispersion of multi-walled carbon nanotubes under ultrasonic cavitation: the aramid III polymer solution with a viscosity of 1000-5000 centipoise is quickly added to the multi-walled carbon nanotube solution obtained in step (1), and ultrasonic cavitation dispersion is performed in a nitrogen closed environment; the ultracavitation dispersion cycle is 15-30 minutes, with a rest period of 30-60 minutes in the middle, and repeated 3-5 cycles; during the nondestructive dispersion process under ultrasonic cavitation, a circulating condenser or an ice water bath is used to cool the outside of the container;
[0007] (4) Post-treatment of the multi-walled carbon nanotube dispersion: the multi-walled carbon nanotube dispersion treated in step (3) is divided into centrifuge tubes, treated at 5000-9000 rpm for 10-20 min, and the precipitate in the centrifuge tube is removed, and the process is repeated 1-3 times;
[0008] (5) Preparation of multi-walled carbon nanotube / aramid III polymer solution: before the polymerization reaction occurs, the multi-walled carbon nanotube dispersion solution is added to the polymerization reaction system, and subjected to secondary ultrasonic dispersion treatment to form a multi-walled carbon nanotube / aramid III polymer solution;
[0009] (6) Multi-walled carbon nanotube composite fibers wrapped with aramid III molecules were prepared by wet spinning.
[0010] According to a specific embodiment of the present invention, the diameter of the multi-walled carbon nanotube is less than 30 nm, the length is 0.5-30 μm, and the number of walls is 2-10.
[0011] Compared with single-walled carbon nanotubes, multi-walled carbon nanotubes are easier to orient during the spinning process, which is beneficial to inducing the orientation of polymer chains during the preparation of aramid fibers, thereby improving the strength and toughness of aramid fibers.
[0012] According to a specific embodiment of the present invention, in step (1), the mass concentration of LiCl in the N,N-dimethylformamide solution containing LiCl is 1-3.5%. The mass concentration of multi-walled carbon nanotubes in the N,N-dimethylformamide solution containing LiCl is 0.05-0.5wt%.
[0013] The invention activates the multi-walled carbon nanotube raw material by dissolving a certain mass of LiCl in a DMAC solution, so that the solvent enters between the multi-walled carbon nanotubes and replaces the air on the surface of the multi-walled carbon nanotubes, thereby opening a path for the aramid III molecules to be adsorbed and wrapped on the surface of the multi-walled carbon nanotubes under subsequent ultrasonic cavitation.
[0014] According to a specific embodiment of the present invention, in step (2), a cell crusher is used to crush the cells, the power of the cell crusher is 800 to 1500 W, and the ultrasonic duration is 15 to 30 minutes.
[0015] In step (2), the inventors found that diluting the aramid III polymer solution to 1000-5000 centipoise can better achieve the wrapping of carbon nanotubes by aramid III.
[0016] In step (3), the carbon nanotubes are non-destructively dispersed under ultrasonic cavitation and the high-speed impact of the bursting bubbles in the solvent on the aramid III molecular chains and the carbon nanotubes is utilized to complete the disentanglement of the carbon nanotubes and the adsorption and encapsulation of the aramid III molecules.
[0017] In step (4), by adding the post-treatment step, the agglomerated carbon nanotubes are removed, which can effectively prevent the carbon nanotubes from causing fiber breakage during the spinning process, thereby improving the strength of the aramid fiber.
[0018] In the technical solution of the present invention, by pre-treatment of carbon nanotubes with activation, combined with lossless dispersion of carbon nanotubes under ultrasonic cavitation and post-treatment steps, the three steps work synergistically to obtain polymer-wrapped carbon nanotubes, thereby achieving monodispersity of carbon nanotubes and improving the strength of the target product composite fiber.
[0019] According to a specific embodiment of the present invention, step (5) specifically comprises the following steps: under nitrogen protection, dissolving LiCl with a mass concentration greater than 1% as a co-solvent in DMAC, adding p-phenylenediamine and 5(6)-amino-2-(p-aminophenyl)benzimidazole monomers, and stirring until all dissolved; cooling, before the polymerization reaction occurs, adding the carbon nanotube dispersion obtained in step (3) to the polymerization reaction system, and subjecting it to a secondary ultrasonic dispersion treatment; immediately adding the first batch of terephthaloyl chloride after the secondary ultrasonic dispersion is completed, and then adding terephthaloyl chloride in batches to obtain a carbon nanotube / aramid III polymerization solution.
[0020] In the technical solution of the present invention, the carbon nanotubes are dispersed once through steps (1) to (4), and the polymer-wrapped carbon nanotubes are obtained, thereby achieving monodispersity of the carbon nanotubes.
[0021] In the prior art, when the carbon nanotube dispersion is added to the polymerization reaction system, it is generally not dispersed or simply mechanically dispersed for uniform mixing. In the technical solution of the present invention, the inventor creatively discovered that secondary ultrasonic dispersion can greatly improve the strength of the target product composite fiber.
[0022] According to a specific embodiment of the present invention, in step (5), the cooling step includes lowering the temperature to below 20°C, preferably below 10°C.
[0023] According to a specific embodiment of the present invention, in step (5), the temperature of the secondary ultrasonic dispersion is maintained below 20° C., preferably below 10° C.; the power is 800 to 1500 W, and the time is 15 to 30 min.
[0024] According to a specific embodiment of the present invention, the mass percentage of carbon nanotubes and aramid III molecules is 0.01wt% to 5wt%;
[0025] Aramid III molecules refer to poly (p-benzimidazole terephthalamide) obtained by low-temperature polymerization of p-phenylenediamine, 5(6)-amino-2-(p-aminophenyl)benzimidazole monomers and terephthaloyl chloride in the system.
[0026] According to a specific embodiment of the present invention, the molar ratio of terephthaloyl chloride, p-phenylenediamine and 5(6)-amino-2-(p-aminophenyl)benzimidazole monomer is 1:(0.8-0.2):(0.2-0.8).
[0027] According to a specific embodiment of the present invention, the first batch of terephthaloyl chloride accounts for 95% to 97% of the total added amount.
[0028] According to a specific embodiment of the present invention, step (6) specifically includes the following steps: the multi-walled carbon nanotube / aramid III polymer solution obtained by the treatment in step (5) is subjected to a spinning process to obtain primary fibers, and heat-treated at 350-410°C under nitrogen protection to obtain the final composite fibers.
[0029] According to a specific embodiment of the present invention, the method for preparing the nascent fiber comprises: pouring the carbon nanotube / aramid III polymer solution obtained in step (4) into a degassing kettle, and performing vacuum treatment for more than 3 hours to remove bubbles in the polymer solution; then squeezing the polymer solution without bubbles from the spinneret through a metering pump and entering a primary coagulation bath of 50% DMAC-distilled water at a flow rate of 3.5 m·min -1 Then, the polymer solution is subjected to high-multiple drawing in a secondary coagulation bath containing 20% DMAC and 80% distilled water, with a drawing ratio of 1.8 to 2.8; the primary fibers are obtained after washing and drying.
[0030] Another object of the present invention is to provide multi-walled carbon nanotube composite fibers wrapped with aramid III molecules prepared by the above preparation method.
[0031] Beneficial Effects
[0032] (1) The present invention develops a non-destructive dispersion method for multi-walled carbon nanotubes for the DMAC / LiCl aramid III system, which maintains the length of the carbon tubes without destroying the carbon tube structure, wraps the polymer chain around the tube body, effectively disperses the tubes longer than 5 microns and prevents reaggregation, thereby optimizing the interface with the polymer;
[0033] (2) The present invention adopts carbon nanotube activation pretreatment-lossless dispersion to prepare carbon nanotube dispersion liquid-carbon nanotube dispersion liquid centrifugal post-treatment, which can realize the wrapping of carbon nanotubes by aramid III molecular chains and effectively remove agglomerated carbon nanotubes;
[0034] (3) In the process of preparing the polymerization solution, the present invention adopts the following order and method of first adding two monomers (p-phenylenediamine and 5(6)-amino-2-(p-aminophenyl)benzimidazole) and completely dissolving them, then cooling them, and then adding the carbon nanotube dispersion solution before the polymerization reaction occurs; the agglomeration of carbon nanotubes caused by solid and highly adhesive monomers can be effectively avoided; under low temperature circulation and nitrogen protection, an external cell crushing device is used for secondary dispersion to further prevent the reagglomeration of carbon nanotubes;
[0035] (4) The present invention optimizes the interface performance, reduces the microstructural defects of the aramid III fiber, and improves the internal stress transfer efficiency of the fiber, thereby obtaining a carbon nanotube / aramid III composite fiber with improved tensile strength and elongation at break;
[0036] (5) The composite fiber obtained by the present invention has a strength greater than 37 cN / dtex and an elongation at break greater than 4%. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 A high-resolution transmission electron microscope image of the carbon nanotube dispersion obtained in step (4) of Example 1;
[0038] Figure 2 Optical images of carbon nanotube / aramid III composite fibers prepared in Example 1 (right picture) and Comparative Example 1 (left picture). DETAILED DESCRIPTION
[0039] The following further exemplifies the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0040] The preparation method of the multi-walled carbon nanotube composite fiber wrapped with aramid III molecules of the present invention specifically comprises: (1) activation pretreatment of the multi-walled carbon nanotubes: dissolving the multi-walled carbon nanotubes in an N,N-dimethylformamide solution containing LiCl, and treating them with a cell crusher for 10 to 30 minutes under N2 protection to obtain a multi-walled carbon nanotube solution;
[0041] (2) Aramid III polymer solution dilution treatment: using the DMAC / LiCl solution of step (1) to dilute the Aramid III polymer solution having a viscosity of 30,000 to 120,000 centipoise to 1,000 to 5,000 centipoise by cell crushing, so that the molecular chains are evenly dispersed in the solvent;
[0042] (3) Lossless dispersion of multi-walled carbon nanotubes under ultrasonic cavitation: The aramid III polymer solution with a viscosity of 1000-5000 centipoise is quickly added to the multi-walled carbon nanotube solution obtained in step (1), and ultrasonic cavitation dispersion is performed in a nitrogen closed environment; the ultracavitation dispersion cycle is 15-30 minutes, with a rest period of 30-60 minutes in the middle, and repeated 3-5 cycles; during the lossless dispersion process under ultrasonic cavitation, a circulating condenser or an ice water bath is used to cool the outside of the container.
[0043] (4) Post-treatment of the multi-walled carbon nanotube dispersion: the multi-walled carbon nanotube dispersion treated in step (3) is divided into centrifuge tubes, treated at 5000-9000 rpm for 10-20 min, and the precipitate in the centrifuge tube is removed, and the process is repeated 1-3 times;
[0044] (5) Preparation of multi-walled carbon nanotube / aramid III polymer solution: before the polymerization reaction occurs, the multi-walled carbon nanotube dispersion solution is added to the polymerization reaction system, and subjected to secondary ultrasonic dispersion treatment to form a multi-walled carbon nanotube / aramid III polymer solution;
[0045] (6) Multi-walled carbon nanotube composite fibers wrapped with aramid III molecules were prepared by wet spinning.
[0046] Step (1) is specifically as follows: dissolving 1-3.5% LiCl in DMAC solution, adding 0.05-0.5wt% multi-walled carbon nanotube powder, and treating with a cell crusher for 10-30 minutes under N2 protection.
[0047] Step (2) is specifically as follows: using the DMAC / LiCl solution of step (1) to dilute the aramid III polymer solution with a viscosity of 30,000 to 120,000 centipoise to 1,000 to 5,000 centipoise by cell crushing, so that the molecular chains are evenly dispersed in the solvent; obtaining the aramid III polymer solution with a viscosity of 1,000 to 5,000 centipoise, so that the molecular chains are evenly dispersed in the solvent. The power of the cell crushing ultrasonic instrument is 800 to 1,500 W, and the ultrasonic time is 15 to 30 minutes.
[0048] Step (3) is specifically as follows: non-destructive dispersion of multi-walled carbon nanotubes under ultrasonic cavitation: the aramid III polymer solution with a viscosity of 1000 to 5000 centipoise is quickly added to the multi-walled carbon nanotube solution obtained in step (1), and ultrasonic cavitation dispersion is performed in a nitrogen closed environment, and the high-speed impact of the bursting bubbles in the solvent on the aramid III molecular chains and the multi-walled carbon nanotubes is used to complete the disentanglement of the multi-walled carbon nanotubes and the adsorption and wrapping of the aramid III molecules. One ultrasonic cycle is 15 to 30 minutes, with a rest period of 30 to 60 minutes, and repeated 3 to 5 cycles. During this process, a circulating condenser or an ice water bath is used to cool the outside of the container.
[0049] Step (4) is specifically as follows: the multi-walled carbon nanotube dispersion treated in step (3) is divided into centrifuge tubes, treated at 5000-9000 rpm for 10-20 min, the sediment in the centrifuge tubes is removed, and the process is repeated 1-3 times until no obvious aggregated particles are visible under an optical microscope.
[0050] Step (5) is specifically as follows: first, under nitrogen protection, dissolving LiCl with a mass concentration greater than 1% as a cosolvent in DMAC, adding p-phenylenediamine and 5(6)-amino-2-(p-aminophenyl)benzimidazole monomers to the above solvent system, and stirring until all dissolved; using a circulating condenser to cool the system, when the temperature is below 20°C, preferably below 10°C, adding the carbon nanotube dispersion obtained in step (2) to the above solution according to 0.01wt% to 5wt% of the aramid III molecule, and performing a secondary ultrasonic dispersion on the mixed solution for 15 to 30 minutes; immediately after the secondary ultrasonic dispersion, adding the first batch of terephthaloyl chloride to rapidly increase the viscosity of the system, then adding the remaining terephthaloyl chloride in batches, and continuing stirring for 1 to 2 hours to obtain a carbon nanotube / aramid III polymer solution with a solution intrinsic viscosity of 30,000 to 120,000 centipoise. No solid is precipitated during this process. The first batch of terephthaloyl chloride should account for 95-97% of the total added amount. Adding too little will not achieve a rapid increase in viscosity, and adding too much is not conducive to a uniform increase in the molecular weight of aramid.
[0051] Step (6) is as follows: pour the multi-walled carbon nanotube / aramid III polymer solution obtained in step (5) into a degassing kettle, and perform vacuum treatment for more than 3 hours to remove bubbles in the polymer solution. Then, the polymer solution without bubbles is squeezed out from the spinneret by a metering pump and enters a primary coagulation bath of 50% DMAC-distilled water at a flow rate of 3.5 m·min -1 Then, the polymer solution was subjected to high-multiple drawing in a secondary coagulation bath of 20% DMAC and 80% distilled water, with a drawing ratio of 1.8 to 2.8. The primary fibers obtained after washing and drying were heat-treated (350 to 410° C.) under nitrogen protection to obtain the final composite fibers.
[0052] Example 1
[0053] (1) Activation pretreatment of multi-walled carbon nanotubes:
[0054] Multi-walled carbon nanotubes (20 nm in diameter, 5 μm in length, and 10 walls) were dissolved in a 2% LiCl solution in N,N-dimethylformamide and treated with a cell crusher for 20 min under N2 protection to obtain activated multi-walled carbon nanotubes. It was observed that the multi-walled carbon nanotube powder had a significant volume expansion phenomenon in the solution.
[0055] (2) Dilution treatment of aramid III polymer solution:
[0056] The aramid III polymer solution with a viscosity of 50,000 centipoise was diluted to 3,000 centipoise using the DMAC / LiCl solution of step (1) by cell crushing.
[0057] (3) Nondestructive dispersion of multi-walled carbon nanotubes under ultrasonic cavitation: A 3000 cps aramid III polymer solution was quickly added to the activated multi-walled carbon nanotube solution and ultrasonic cavitation dispersion was performed in a nitrogen closed environment. The ultrasonic cycle lasted 20 min, with a 40 min break in between, and repeated 4 cycles.
[0058] (4) The multi-walled carbon nanotube dispersion treated in step (3) was divided into centrifuge tubes and treated at 8000 rpm for 15 min to remove the sediment in the centrifuge tubes. This step was repeated once until no obvious aggregated particles were visible under an optical microscope. Figure 1 As shown, the surface of the multi-walled carbon nanotubes in the dispersion is evenly wrapped with aramid III molecules, which effectively avoids contact between the tube walls and ensures that the multi-walled carbon nanotubes do not aggregate again during storage and use; at the same time, the wrapping layer has a high degree of order and can be used as a template to induce the orientation of polymer chains, optimize the internal structure of the fiber, and improve the mechanical properties of the composite fiber.
[0059] (5) Preparation of multi-walled carbon nanotube / aramid III polymer solution: Under nitrogen protection, 2% LiCl was dissolved in DMAC as a cosolvent, p-phenylenediamine and 5(6)-amino-2-(p-aminophenyl)benzimidazole monomers were added to the above solvent system, and stirred until they were completely dissolved; the system was cooled to 10° C. using a circulating condenser, and the carbon nanotube dispersion obtained in step (2) was added to the above solution according to 0.1wt% of the aramid III molecule, and the mixed solution was subjected to secondary ultrasonic dispersion, the dispersion time was 20 min, and the power was 800 W; after the secondary ultrasonic dispersion, the first batch of terephthaloyl chloride was immediately added to rapidly increase the viscosity of the system, and then the remaining terephthaloyl chloride was added in batches, and the stirring was continued for 2 hours to obtain a carbon nanotube / aramid III polymer solution with a solution intrinsic viscosity of 50,000 centipoise. No solid was precipitated during this process. The molar ratio of terephthaloyl chloride, p-phenylenediamine and 5(6)-amino-2-(p-aminophenyl)benzimidazole monomers is 1:0.8:0.2; the first batch of terephthaloyl chloride should account for 97% of the total added amount.
[0060] (6) Prepare the carbon nanotube / aramid III composite fiber by wet spinning: pour the carbon nanotube / aramid III polymer solution obtained in step (3) into a degassing kettle, and vacuumize for 4 hours to remove the bubbles in the polymer solution. Then, the polymer solution without bubbles is squeezed out from the spinneret by a metering pump and enters a primary coagulation bath of 50% DMAC-distilled water at a flow rate of 3.5 m·min -1Then, the polymer solution was drawn in a secondary coagulation bath of 20% DMAC and 80% distilled water at a high draw ratio of 2. The primary fibers obtained after washing and drying were heat treated at 370°C under nitrogen protection to obtain the final composite fibers. The strength was 37.0 cN / dtex and the elongation at break was 4.0%.
[0061] Example 2
[0062] The other conditions are the same as those in Example 1, except that the type of raw material multi-walled carbon nanotubes is (diameter 10, length 10 μm, wall number 5). The carbon nanotube dispersion treated in step (3) is divided into centrifuge tubes, treated at 8000 rpm for 15 min, and the precipitate in the centrifuge tube is removed. This step is repeated twice. The molar ratio of terephthaloyl chloride, p-phenylenediamine and 5(6)-amino-2-(p-aminophenyl)benzimidazole monomers is 1:0.7:0.3; the result is a strength of 37.2 cN / dtex and an elongation at break of 4.1%.
[0063] Example 3
[0064] The other conditions were the same as those in Example 1, except that the type of raw material multi-walled carbon nanotubes was (diameter 5, length 10 μm, number of walls 10). The carbon nanotube dispersion treated in step (3) was divided into centrifuge tubes and treated at 8000 rpm for 15 min. The sediment in the centrifuge tubes was removed, and this step was repeated twice. Under nitrogen protection, 3.5% LiCl was dissolved in DMAC as a co-solvent, p-phenylenediamine and 5(6)-amino-2-(p-aminophenyl)benzimidazole monomers were added to the above solvent system, and stirred until they were completely dissolved; the system was cooled to 10° C. using a circulating condenser, the carbon nanotube dispersion obtained in step (2) was added to the above solution according to 0.075wt% of the aramid III molecule, and the mixed solution was subjected to secondary ultrasonic dispersion, the molar ratio of terephthaloyl chloride, p-phenylenediamine and 5(6)-amino-2-(p-aminophenyl)benzimidazole monomers was 1:0.7:0.3; the result was a strength of 37.5 cN / dtex and an elongation at break of 4.2%.
[0065] Comparative Example 1
[0066] The other conditions are the same as those in Example 1, except that steps (3) and (4) are not included, and the aramid III polymer solution of step (2) is added to the carbon nanotube solution of step (1) to obtain a carbon nanotube dispersion. The strength of the prepared composite fiber is 29 cN / dtex and the elongation at break is 2.8%.
[0067] Figure 2The left side shows the multi-walled carbon nanotube / aramid fiber obtained by post-processing the carbon nanotube dispersion; the right side shows the multi-walled carbon nanotube / aramid fiber obtained by post-processing the multi-walled carbon nanotube dispersion. It can be seen that after post-processing, the broken fibers are significantly reduced, the frizziness of the fiber surface is significantly reduced, and the strength of the aramid fiber can be effectively improved.
[0068] Comparative Example 2
[0069] The other conditions are the same as those in Example 1, except that step (1) is omitted, and the carbon nanotubes are directly added to the diluted aramid III polymer solution for lossless dispersion. The strength of the prepared composite fiber is 34 cN / dtex, and the elongation at break is 3.3%.
[0070] Comparative Example 3
[0071] The other conditions are the same as those in Example 1, except that steps (1), (3) and (4) are omitted, and the carbon nanotubes are directly added to the diluted aramid III polymer solution to obtain a carbon nanotube dispersion. The strength of the prepared composite fiber is 27 cN / dtex and the elongation at break is 2.5%.
[0072] Comparative Example 4
[0073] The other conditions were the same as those in Example 1, except that no secondary ultrasonic dispersion was performed. The strength of the prepared composite fiber was 35 cN / dtex, and the elongation at break was 3.4%.
[0074] Comparative Example 5
[0075] The other conditions were the same as those in Example 1, except that the secondary ultrasonic dispersion was replaced by ordinary mechanical stirring. The strength of the prepared composite fiber was 33 cN / dtex, and the elongation at break was 3.5%.
[0076] The mechanical test results of Examples 1-3 and Comparative Examples 1-5 are summarized in Table 1:
[0077] Table 1
[0078]
[0079] It can be seen from the result data of Comparative Examples 1-3 and Example 1 that the three steps of step (1) activation pretreatment, step (3) lossless dispersion of carbon nanotubes under ultrasonic cavitation and step (4) post-treatment work synergistically to greatly improve the mechanical properties of the obtained composite fiber.
[0080] It can be seen from the result data of Comparative Examples 4-5 and Example 1 that the use of secondary ultrasonic dispersion can obtain composite fibers with better mechanical properties than the conventional dispersion or no dispersion.
[0081] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.
[0082] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.
Claims
1. A method for preparing multi-walled carbon nanotube composite fibers wrapped with aramid III molecules, characterized in that: The specific steps include: (1) Activation pretreatment of multi-walled carbon nanotubes: dissolving the multi-walled carbon nanotubes in a N,N-dimethylformamide solution containing LiCl, and treating them with a cell crusher for 10 to 30 minutes under N2 protection to obtain a carbon nanotube solution; (2) Aramid III polymer solution dilution treatment: using a DMAC / LiCl solution of the same concentration as in step (1) to dilute the Aramid III polymer solution having a viscosity of 30,000 to 120,000 centipoise to 1,000 to 5,000 centipoise by cell crushing or mechanical stirring, so that the molecular chains are uniformly dispersed in the solvent; (3) Nondestructive dispersion of carbon nanotubes under ultrasonic cavitation: the aramid III polymer solution with a viscosity of 1000 to 5000 centipoise is quickly added to the carbon nanotube solution obtained in step (1), and ultrasonic cavitation dispersion is performed in a nitrogen closed environment; the ultrasonic cavitation dispersion cycle is 15 to 30 minutes, with a rest period of 30 to 60 minutes, and repeated 3 to 5 cycles; during the nondestructive dispersion process under ultrasonic cavitation, a circulating condenser or an ice water bath is used to cool the outside of the container; (4) Post-treatment of the multi-walled carbon nanotube dispersion: the multi-walled carbon nanotube dispersion treated in step (3) is divided into centrifuge tubes, treated at 5000-9000 rpm for 10-20 min, and the precipitate in the centrifuge tube is removed, and the process is repeated 1-3 times; (5) Preparation of multi-walled carbon nanotube / aramid III polymer solution: before the polymerization reaction occurs, the multi-walled carbon nanotube dispersion solution is added to the polymerization reaction system, and subjected to secondary ultrasonic dispersion treatment to form a multi-walled carbon nanotube / aramid III polymer solution; (6) The multi-walled carbon nanotube composite fiber wrapped with the aramid III molecules is prepared by wet spinning.
2. The preparation method according to claim 1, characterized in that: The multi-walled carbon nanotube has a diameter of less than 30 nm, a length of 0.5 to 30 μm, and 2 to 10 walls.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass concentration of LiCl in the N,N-dimethylformamide solution containing LiCl is 1 to 3.5%.
4. The preparation method according to claim 1, characterized in that: In step (1), the mass concentration of the multi-walled carbon nanotubes in the N,N-dimethylformamide solution containing LiCl is 0.05-0.5 wt %.
5. The preparation method according to claim 1, characterized in that: Step (5) specifically comprises the following steps: under nitrogen protection, dissolving LiCl with a mass concentration greater than 1% as a co-solvent in DMAC, adding p-phenylenediamine and 5(6)-amino-2-(p-aminophenyl)benzimidazole monomers, and stirring until all are dissolved; cooling, before the polymerization reaction occurs, adding the multi-walled carbon nanotube dispersion obtained in step (3) to the polymerization reaction system, and subjecting it to secondary ultrasonic dispersion treatment; immediately adding the first batch of terephthaloyl chloride after the secondary ultrasonic dispersion is completed, and then adding terephthaloyl chloride in batches to obtain a multi-walled carbon nanotube / aramid III polymerization solution.
6. The preparation method according to claim 5, characterized in that: The mass percentage of the multi-walled carbon nanotubes and the aramid III molecules is 0.01wt% to 5wt%.
7. The preparation method according to claim 5, characterized in that: The molar ratio of terephthaloyl chloride, p-phenylenediamine and 5(6)-amino-2-(p-aminophenyl)benzimidazole monomers is 1:(0.8-0.2):(0.2-0.8).
8. The preparation method according to claim 5, characterized in that: The first batch of terephthaloyl chloride accounts for 95wt% to 97wt% of the total added amount.
9. The preparation method according to claim 1, characterized in that: Step (6) specifically includes the following steps: spinning the multi-walled carbon nanotube / aramid III polymer solution obtained in step (5) to obtain primary fibers, and heat treating at 350-410° C. under nitrogen protection to obtain the final composite fibers.
10. The preparation method according to claim 9, characterized in that: The method for preparing the nascent fiber comprises: pouring the multi-walled carbon nanotube / aramid III polymer solution obtained in step (4) into a degassing kettle, and performing vacuum treatment for more than 3 hours to remove bubbles in the polymer solution; then squeezing the polymer solution without bubbles from a spinneret through a metering pump and entering a primary coagulation bath of 50% DMAC-distilled water at a flow rate of 3.5 m·min -1 Then, the polymer solution is subjected to high-multiple drawing in a secondary coagulation bath containing 20% DMAC and 80% distilled water, with a drawing ratio of 1.8 to 2.8; the primary fibers are obtained after washing and drying.
11. A multi-walled carbon nanotube composite fiber wrapped with aramid III molecules prepared according to the preparation method according to any one of claims 1 to 10.
Citation Information
Patent Citations
Preparation method of carbon nanotube aramid fiber and carbon nanotube aramid fiber
CN114197076A
Method for preparing heterocyclic aromatic polyamide spinning solution
CN102505151A
Aramid 1313 / MWCNT (Multi-Walled Carbon Nanotube) nano fibers and preparation method thereof
CN102877152A
Method for improving concentration of monodisperse carbon nanotube dispersion liquid
CN111747400A
Olefinic carbon material dispersion liquid and application thereof
CN113248739A